Penggunaan Atraktor Buatan yang Ramah Lingkungan dalam Pemanenan Anakan Udang Lobster Laut (Panulirus spp) - Musbir Musbir; Sudirman Sudirman; Mahfud Palo (Hasanuddin University, 2014)
Spiny lobster (Panulirus spp) is one of important commodities in Bulukumba Regency. The lobsters used for aquaculture were obtained from the wild catch in the sea. The purpose of this study was to develop artificial gear to attract the lobster seed to beeasily caught. The research was conducted in marine coastal of Ujung Bulu, Bulukumba Regency, South Sulawesi from July to October 2013. There are three artificial attractors that consisted of light attractor, trap shelter attractor, and shelter benthic attractor. Results showed that the spiny lobster catches from artificial attractor consisted of 47.5 % of pearl lobster (Panulirus ornatus), 25.8% of sand lobster (P. homarus), 21.2 % of bamboo lobster (P. versi color), 5.6% of stone lobster (P. penicilatus). The carapace length of both pearl lobsterand sand lobster ranged from 2,6 to 6,0 cm, which were longest among the other lobsters..